The Argentina Paradox: Microexplanations and macropuzzles - Alan M. Taylor (Latin American Economic Review, 2018)
The economic history of Argentina presents one of the most dramatic examples of divergence in the modern era. What happened and why? This paper reviews the wide range of competing explanations in the literature and argues that, setting aside deeper social and political determinants, the various economic mechanisms in play defy the idea of a monocausal explanation.
Keywords: F43; N16; O11; O54; O57; P52; 330; Latin America; Growth; Trade; Finance; Institutions; Policies; Divergence